Analysis Of Financial Performance Of The Regional Government Of Lumajang District For The 2020-2022 Budget Year - Wiyanti , Ani; Rista, Indriany; Tyas , Mohamad Adiet Sandi; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research intends to evaluate the financial performance of the Lumajang Regency Regional Government for the 2020-2022 period. The research approach is quantitative descriptive using secondary data from the 2020-2022 Lumajang Regency APBD. The financial performance of the Lumajang Regency Regional Government in terms of the average figure for the Degree of Fiscal Decentralization Ratio of 15.18% is in the Low category, the Regional Financial Independence Ratio of 17.91% is in the Very Low category with an Instructive relationship pattern, the Financial Dependency Ratio The regional level is 84.82% which is categorized as high level of dependency, the PAD Effectiveness Ratio is 105.64% with the categorization of Very Effective, the Regional Financial Efficiency Ratio is 98.96% which is classified as Less Efficient, and the Capital Expenditure Ratio is still 10.99%. meets standards that are in the range of 5-20%. Based on these findings, it can be concluded that overall the financial performance of the Lumajang Regency Regional Government has not yet reached optimality. However, the calculation results show that there is an increase in financial performance every year